Analyzing the integration of Islamic character values into primary school curricula in Aceh - Mukhlis, Mukhlis; Satori, Djam’an; Prihatin, Eka; Suryadi, Suryadi (Universitas Jambi, Indonesia, 2025)
This study aims to analyze the integration of Islamic character values into the primary school curriculum in Pidie Jaya, Aceh, and to propose a conceptual framework for systematically embedding these values within educational practices. A qualitative case study approach was employed, involving in-depth interviews with school principals, teachers, education officers, and students, as well as classroom and school observations, and the analysis of documents such as lesson plans, syllabi, and school programs. The findings show that Islamic values such as honesty, discipline, responsibility, religiosity, cooperation, respect, and cleanliness are integrated across subjects, daily routines, and school culture. Teachers play a pivotal role through contextual teaching, role modeling, and practices like prayers and Qur’anic recitation. Strong school leadership, governance, and collaboration with parents and community institutions further support the development of character. However, challenges persist, including variations in teacher competence, limited resources in rural areas, and inconsistent reinforcement at home. The study recommends strengthening teacher professional development, enhancing parental engagement, and integrating digital moral literacy.